Feasibility studies and dynamics of catalytic liquid phase esterification reactions in a micro plant - Kulkarni, A. A.; Zeyer, K. -P.; Jacobs, T.; Kaspereit, M.; Kienle, Achim (Chemical Engineering Journal, 2008)
We present a new micro reactor concept which is suitable for investigations of heterogeneously catalyzed liquid phase reactions. In the set-up two reactants are mixed in a commercially available interdigital micro mixer. The outlet of the micro mixer is connected to a modular micro reactor that consists of stacked plates. Each plate contains a milled meandering channel filled with catalyst beads. By using a variable number of plates the residence time can be manipulated and thus adjusted for a specific task. The synthesis of butyl acetate is considered as a model reaction since it has been investigated in detail in conventional reaction systems. In a first step, some experimental results of the heterogeneously catalyzed reaction are presented. In the second part, the set-up is operated as a chromatographic reactor. Dynamic behaviour is investigated applying the frontal analysis mode and the elution chromatography mode. (c) 2007 Elsevier B.V. All rights reserved.
9th International Conference on Microreaction Technology, Berlin, GERMANY, SEP 06-08, 2006
Keywords: chromatographic reactor; heterogeneous catalysis; integrated process; modular micro reactor